Development and Validation of an RP-HPLC Method for the Determination of Tiazotic Acid and Its Impurity with Application to Tablet Analysis - Ivković, Branka; Turković, Nemanja; Turković, Milena; Čudina, Olivera; Crevar, Milkica (Archives of Pharmacy, 2026)
A simple and precise RP-HPLC method was developed and validated for the determination of tiazotic acid and its impurity, 3-methyl-1,2,4-triazole-5-thione, with application to tablet analysis. Chromatographic analysis was performed using a Hypersil GOLD aQ C18 column (150 × 4 mm, 3 µm) under isocratic elution conditions with a mobile phase consisting of phosphate buffer (pH 3.3) and methanol in a ratio of 99:1 (v/v), at a flow rate of 1 mL/min and a column temperature of 30 °C. Detection was carried out at 220 nm. The developed method was validated in accordance with ICH guidelines. The following analytical parameters were evaluated during validation: selectivity, linearity, precision, accuracy, robustness, and the limit of quantification (LOQ) for the investigated impurity. The method demonstrated linearity over the concentration range of 0.139–0.238 mg/mL (r = 0.9992) for tiazotic acid and 0.091–1.56 µg/mL (r = 0.9998) for the impurity. Good precision (RSD < 2% for tiazotic acid and RSD < 10% for the impurity), accuracy (recovery in the range of 98–102% and 70–130% for the impurity), and robustness were confirmed. The impurity 3-methyl-1,2,4-triazole-5-thione was detected in tiazotic acid tablets; however, its content was below the limit of quantification (LOQ) of the proposed method (0.091 µg/mL).